Audio-tactile graphics for arts education: development of prototypes for accessibility for blind people (Human Factors in Design, 2023)
Communication in the classroom is mostly done through the domain of the visual image, where blind students often do not have access to the content. From this context, the aim of this article is to present the development of two prototypes of audio-tactile graphics, designed as assistive technology for arts teaching. The development of the prototype comprises six phases, from image selection to finalization of the audio-tactile graphics. The prototypes developed prove to be important to provide accessibility and the step-by-step development serves as a subsidy and basis for other professionals in the area.
Keywords: audio-tactile graphics; accessibility; assistive technology